2020
DOI: 10.5114/jcb.2020.100385
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy in head and neck malignancies: Indian Brachytherapy Society (IBS) recommendations and guidelines

Abstract: Purpose Brachytherapy (BT) forms major treatment modality in squamous cell carcinoma of head and neck cancers (HNC). However, there is a dearth of literature and guidelines for the use in various indications. High-dose-rate brachytherapy (HDR-BT) in Indian scenario is an important treatment modality, and the recommendations in this guidelines aim to provide the necessary recommendations for the use of HDR-BT for uniform application across the country in patients with HNC. Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In patients with oral cancer, after RT, the low stimulated salivary flow was explained by secretion hypofunction, severe atrophy, interstitial fibrosis, and loss of parenchyma of salivary glands [39,40]. This underlined that all patients in the xerostomia [41] group had a decreased SSF, which was considered an important marked sign in patients with oral cancer after RT treatments [42,43]. At 3 months, there was a significant reduction in unstimulated (0.346 mL/min) and stimulated (0.80 mL/min) SRF, the unstimulated flow rate continued to decrease further until 6 months (0.295 mL/min), and an increase in SFR (0.91 mL/min) was recorded.…”
Section: Discussionmentioning
confidence: 97%
“…In patients with oral cancer, after RT, the low stimulated salivary flow was explained by secretion hypofunction, severe atrophy, interstitial fibrosis, and loss of parenchyma of salivary glands [39,40]. This underlined that all patients in the xerostomia [41] group had a decreased SSF, which was considered an important marked sign in patients with oral cancer after RT treatments [42,43]. At 3 months, there was a significant reduction in unstimulated (0.346 mL/min) and stimulated (0.80 mL/min) SRF, the unstimulated flow rate continued to decrease further until 6 months (0.295 mL/min), and an increase in SFR (0.91 mL/min) was recorded.…”
Section: Discussionmentioning
confidence: 97%
“…Available recommendations for IRT in H&N cancers underline that DNR should be below 0.35 [22]. Available dosimetric data published in a retrospective series showed that higher DNR values are not associated with an increase in terms of adverse events [16].…”
Section: Discussionmentioning
confidence: 99%
“…In early-stage node negative disease, 45-54 Gy, 4-4.5 Gy per fraction in 10-12 fractions may be given (BED, 65-84 Gy) as radical treatment. Recommended dose for HDR brachytherapy boost after external irradiation is 16-22 Gy, 4-4.5 Gy per fraction in 4-5 fractions (BED, 26-32 Gy) in T1 disease, while in T2 disease, the recommended dose is 22-26 Gy, 4-4.5 Gy per fraction in 5-6 fractions (BED, 32-40 Gy) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%